Organizational Development: The Management of Change in Industrial Organizations in Nigeria - Oparanma, Austn O; Zeb-Obipi, Isaac (International Journal of Asian Social Science, 2012)
This study is centered on the management of change in industrial organizations in Port Harcourt, Nigeria. To achieve the purpose of the study, two null hypotheses were stated, a sectional survey was conducted using data which were from the Nigerian Engineering works, Port Harcourt, with the aid of questionnaire and personal discussions. The response of the questionnaire services serve as the basic element of the study. The instrument for collecting the primary data consisted of 120 copies of questionnaire administered personally to the respondents, which constituted the sample size. The hypotheses were tested with the use of Chi-square (X2) formula. The findings of the research revealed that change management is a great phenomenon that enhances the performance of the industrial organizations and that if more attentions are given, industrial organizations definitely will have a good standard. We therefore recommend that the management should encourage change in the industrial organizations and that industrial organizations are better of with innovative process on products and procedures of production.